DNA Barcode Characteristic of Dendrobium crumenatum based on ITS2 - Fitri, Nurfajri Eka; ., Mukhamad Su’udi; Ikrimah, Sindhi Wahidatul (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2024)
Dendrobium crumenatum, known as the pigeon orchid, is a type of orchid that is used as medicine by local people. Identification of D.crumenatum has limitations because it is similar to the orchid species D. heterocarpum. DNA barcoding is an alternative technique for identifying D.crumenatum using molecular markers. One of the molecular markers that is reliable and widely used in DNA barcoding is ITS2. This study aims to identify the ITS2 sequence as a molecular barcode effective for D.crumenatum. Genomic DNA isolation of Dendrobium crumenatum was carried out using the Cetyl Trimethyl Ammonium Bromide (CTAB) method and DNA amplification using PCR. The results showed that DNA barcoding research using the ITS2 sequence in D. crumenatum provides specific results to distinguish D. crumenatum from other Dendrobium species. The similarity in flower morphology in D. crumenatum and D. formosum proposed as the cause of close proximity shown in phylogenetic tree. Based on these results, the ITS2 sequence is highly recommended as a molecular marker for barcoding orchids, especially D. crumenatum since its capability for differentiating between species with morphological similarities. Key words: Dendrobium crumenatum, DNA Barcoding, ITS2